Seasonal distribution and nature reserve planning of Indo-Pacific humpback dolphins in the Pearl River estuary from South China Sea - Xikai Tang; Dingyu Luo; Xian Sun; Bin Sun; Lang Guo; Hongri Wang; Nuoyan Huang; Zhiwei Liu; Yifei Liu; Nan Wang; Yuping Wu (Global Ecology and Conservation, 2025)
Understanding habitat use patterns and assessing diffusion status are essential for effective conservation of cetaceans, particularly the Indo-Pacific humpback dolphins (Sousa chinensis) in the Pearl River Estuary (PRE), where habitat decline is contributing to demographic decline. This study provides a seasonal evaluation of habitat suitability and distribution for PRE humpback dolphins using five years of boat-based field survey data from 2019 to 2023. Our results indicate significant seasonal variations in dolphin habitat. The core habitat in eastern PRE increased from 738 km² in the dry season to 822 km² in the wet season, while the middle PRE core habitat decreased from 408 km² to 213 km². During the dry season, dolphin habitats are more dispersed and closer to the estuary's interior, whereas they become more concentrated in the wet season. This dynamic spatial redistribution reflects responses to seasonal changes in water quality and prey availability. Key environmental factors influencing habitat distribution include salinity, chlorophyll a concentration, water depth, and dissolved oxygen, with varying impacts across seasons. Additionally, precipitation and monsoons play significant roles in predicting dolphin habitats throughout the year. We recommend establishing dynamic protection zones in areas with seasonal changes in dolphin presence to enable adaptive management strategies. This study underscores the need for ongoing research and monitoring to clarify the interactions between climatic variables and the ecological integrity of marine habitats.